Evolution of Broadcast Content Distribution - Beutler, Roland (Springer International Publishing : Imprint: Springer, 2017)
This book discusses opportunities for broadcasters that arise with the advent of broadband networks, both fixed and mobile. It discusses how the traditional way of distributing audio-visual content over broadcasting networks has been complemented by the usage of broadband networks. The author shows how this also gives the possibility to offer new types of interactive or so-called nonlinear services. The book illustrates how change in distribution technology is accelerating the need for broadcasters around the world to adapt their content distribution strategy and how it will impact the portfolios of content they offer. Outlines the shift in broadcast content distribution paradigms and related strategic issues Provides an overview of the new broadcasting ecosystem encompassing new types of content, user habits, expectations, and devices Discusses complementary usage of different distribution technologies and platforms.